Graphene decorated polymeric flexible materials for lightweight high areal energy lithium-ion batteries. (December 2019) - Aslam, Sehrish; Sagar, Rizwan Ur Rehman; Liu, Yixin; Anwar, Tauseef; Zhang, Liwen; Zhang, Min; Mahmood, Nasir; Qiu, Yejun
Graphical abstract: Highlights: Laser induced room temperature synthesis of graphene foam on polyimide. LIGF is deployed directly as flexible and binder free anode for lithium-ion battery. LIGF delivered high areal capacity of 280 μA h cm −2 and excellent rate capability. Growth of LIGF in furrows and ridges provide high mas transport and ionic storage. Current anode design allows flexible and wearable energy devices for insect robots. Abstract: High energy density lightweight batteries are required to revolutionize the future electronics and electric vehicles, thus, a lightweight and flexible material having the ability to carry high energy is the need of the hour. Herein, we have used laser-induced graphene foam (LIGF), grown at polyimide, directly as a self-sustaining binder-free anode material for lithium-ion batteries. The migration of the electrons on the LIGF grown finally on the one side of polyimide makes it possible to directly implant as a device, for a proof of concept, a folded specimen of LIGF is used as an anode. The initial areal capacity of ∼203 μAhcm −2 for as-grown LIGF increases to 280 μA hcm −2 upon annealing at 400 °C because of the improved graphitization. Stable rate performance is observed for 100 cycles at a current density of 0.1 mAcm −1 with average Coulombic efficiency of 99%. The electrochemical impedance spectroscopy hint that the conductivity of the annealed specimen is increased subsequently favors faster electronic flow on the one side of a non-conducting polymer. The present study paves a path towards future LIGF based lightweight lithium-ion batteries and also enables flexible wearable high energy density storage devices.